Enhanced Chondrogenic Capacity of Mesenchymal Stem Cells After TNFα Pre-treatment - Voskamp, Chantal; Koevoet, Wendy J. L. M.; Somoza, Rodrigo A.; Caplan, Arnold I.; Lefebvre, Véronique; van Osch, Gerjo J. V. M.; Narcisi, Roberto (Frontiers in Bioengineering and Biotechnology, 2020)
Mesenchymal stem cells (MSCs) are promising cells to treat cartilage defects due to their chondrogenic differentiation potential. However, an inflammatory environment during differentiation, such as the presence of the cytokine TNFα, inhibits chondrogenesis and limits the clinical use of MSCs. On the other hand, it has been reported that exposure to TNFα during in vitro expansion can increase proliferation, migration and the osteogenic capacity of MSCs and therefore can be beneficial for tissue regeneration. This indicates that the role of TNFα on MSCs may be dependent on the differentiation stage. To improve the chondrogenic capacity of MSCs in the presence of an inflamed environment, we aimed to determine the effect of TNFα on the chondrogenic differentiation capacity of MSCs. Here, we report that TNFα exposure during MSC expansion increased the chondrogenic differentiation capacity regardless of the presence of TNFα during chondrogenesis and that this effect of TNFα during expansion was reversed upon TNFα withdrawal. Interestingly, pre-treatment with another pro-inflammatory cytokine, IL-1β, did not increase the chondrogenic capacity of MSCs indicating that the pro-chondrogenic effect is specific for TNFα. Finally, we show that TNFα pre-treatment increased the levels of SOX11 and active β-catenin suggesting that these intracellular effectors may be useful targets to improve MSC-based cartilage repair. Overall, these results suggest that TNFα pre-treatment, by modulating SOX11 levels and WNT/β-catenin signaling, could be used as a strategy to improve MSC-based cartilage repair.